Analisis Efektivitas Sistem Pengendalian Internal Dalam Mengatasi Kredit Macet Dengan Menerapkan Prinsip â€œPang Pade Payuâ€ Pada BUMDES Sidi Amerta - Erawati, Made; Atmadja, Anantawikrama Tungga (Vokasi : Jurnal Riset Akuntansi, 2020)
BUMDes Sidi Amerta is an official institution with a village managed by a joint and legal entity village, one of the operations of which is a savings and loan business. This study was intended to find out (1) How the internal control system applied by the Sidi Amerta Village Business Entity in implementing bad credit, (2) How to apply the "pang pade payu" principle to get bad credit at the Sidi Amerta BUMDes. In this study using a descriptive method with a qualitatitive approach. The data collection method was obtained through the observation method, the interview method, and the documentation method conducted at BUMDes Sidi Amerta. The data processing that has been collected is then completed through data reduction, data presentation and making conclusion.The results showed that the implementation of (1) the internal control system at BUMDes Sidii Amerta was quite good with supervision carried out effectively, but the management's knowledge in the field of accounting allowed for fraud; (2) The effectiveness of the application of the principle of "pang pade payu" for bad loans is quite effective, because it uses a family that makes the recipients get relief in paying for their needs without protection increasing the importance of care to pay for their needs; (3) Suggestions for follow-up actions carried out are more selective in granting loans in accordance with the ability of the credit assistance.